PERKAWINAN BEDA AGAMA PASCA SEMA NO.2 TAHUN 2023 (Analisa Yuridis Sosiologis Perkawinan Beda Agama di Indonesia) - ROPIAH, SITI (Universitas Islam Madura, 2024)
A small number of marriages of different religions in Indonesia are carried out because they have received court approval. The reason used as a basis is because religion is an absolute right of every person that cannot be forced and marriage is a citizen's right guaranteed by the State. This reason encourages researchers to study the problems of interfaith marriages mentioned above. The research method currently being carried out is library research, namely research that applies a conceptual approach by expressing various opinions of legal experts regarding marriage between people of different religions. The results of the research show that inter-religious marriages have two different interpretations: first, the marriage is declared valid and can be carried out based on 4 grounds, namely: 1) interpretation of the Marriage Law article 2, that marriages of different religions may be carried out, 2) The reason for submission is based on Supreme Court decision Number. 1400 of 1986, 3) Article 35 of the Adminduk Law, and 4) based on the reason that people whose marriages are not registered at the KUA, can be allowed to be united in one family and have a KTP with marital status written on it, as per the regulations in the Minister of Home Affairs Regulation No. 9 of 2016. Second, some reject interfaith marriages based on: 1) Article 2 of Law no. 1 of 1974 (with the interpretation that marriage must be of the same religion), 2) Article 4 of the KHI which prohibits marriages other than Muslims, 3) MUI Fatwa No. 4 of 2005, 4) Results of NU Congress No. 28 of 1989 and Tarjih Muhammadiyah No. 22 of 1989, 5) MK no. 56/PUU-XV/2017.